Struktur Dan Fungsi Protein Kolagen - Katili, Abubakar Sidik (Jurnal Pelangi Ilmu, 2009)
Protein is a macromolecule having base goods 20 kinds of amino acid. Protein has main role in biological system in every organism, some between it is as catalyst, as conveyor and depositor of other molecule like oxygen, supports mechanically impenetrability system (immunity) body, yields movement of body, as transmitor movement of nerve and controls growth and development. Existence of the biological function becomes base in classification for protein. This article explained about one of type from protein namely collagen. Solution about collagen in this article include;covers special and common of collagen and collagen structure. Conclusion from this article inter alia: collagen is material having strength of spread and structure which is in the form of fibre, collagen is main fibre component in bone, tooth, cartilage, skin layer in derm, tendon cartilage and eyepiece, collagen fibril consisted of polypeptide unit sub called tropokolagen which consist of three polypeptide chains which called helix, existence of collagen that is unsatisfying perfect in the forming can cause disease like scurvy, that marked by venous damage and skin structure.